2019
DOI: 10.1029/2019pa003734
|View full text |Cite
|
Sign up to set email alerts
|

The Medieval Climate Anomaly in the Mediterranean Region

Abstract: The Medieval Climate Anomaly (MCA) is a preindustrial phase of pronounced natural climate variability with a core period from 1000 to 1200 CE. The paper presents a synthesis that integrates palaeotemperature records from the Greater Mediterranean Region encompassing the past 1,500 years based on multiproxy data from 79 published land and marine sites. MCA warming dominated the Western Mediterranean (Iberia, NW Africa) as well as the northern land areas of the Central and Eastern Mediterranean region. MCA cooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 270 publications
(323 reference statements)
4
28
0
1
Order By: Relevance
“…The findings encourage further consideration of the Little Ice Age concept in the High Atlas setting. Overall, the prevailing paradigm in Morocco and the Western Mediterranean more widely is of a dry MCA and a wet Little Ice Age (Moreno et al 2012;Fletcher and Zielhofer 2013;Lüning et al 2017Lüning et al , 2019. This paradigm is supported by many Moroccan records, notably speleothems, lake-levels and tree-rings in the Middle Atlas (Esper et al 2007;Détriché et al 2009;Wassenburg et al 2013), and is broadly consistent with long term changes observed at Oukaïmeden.…”
Section: Snowpack Dynamics In the High Atlassupporting
confidence: 72%
“…The findings encourage further consideration of the Little Ice Age concept in the High Atlas setting. Overall, the prevailing paradigm in Morocco and the Western Mediterranean more widely is of a dry MCA and a wet Little Ice Age (Moreno et al 2012;Fletcher and Zielhofer 2013;Lüning et al 2017Lüning et al , 2019. This paradigm is supported by many Moroccan records, notably speleothems, lake-levels and tree-rings in the Middle Atlas (Esper et al 2007;Détriché et al 2009;Wassenburg et al 2013), and is broadly consistent with long term changes observed at Oukaïmeden.…”
Section: Snowpack Dynamics In the High Atlassupporting
confidence: 72%
“…It has been shown that warmer and wetter conditions favored the flea burden and host abundance (black rats or great gerbil) in the case of bubonic plague (Stenseth et al, 2006). While regional conditions may have promoted the second plague outbreak in Central Asia (Stenseth et al, 2006), the "pre" Little Ice Age (AD 1300-1550) was a wetter and cooler period in both Europe and Eurasia (Jones et al, 2001(Jones et al, , 2006Griggs et al, 2007;Kaniewski et al, 2011;Xoplaki et al, 2018;Lüning et al, 2019). Because rat/gerbil and flea blooms are favored by climate conditions not recorded from Eurasia to Europe (Lionello, 2012;Kushnir and Stein, 2019), and as rats were scarce in northern Europe during the plague outbreaks (Davis, 1986), the epidemics may have mostly spread via humanto-human transmission.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, is the only direct information on glacial melting during the MCA in the Pyrenees, confirming the negative effect of the medieval warming for the survival of glaciers, even at high elevations. Morellón et al (2011) reported low lake levels and saline conditions in the Estanya Lake, Pre-Pyrenees, during medieval times, particularly between 1150 and 1300 CE, most likely due to the persistence of positive Atlantic Multidecadal Oscillation and North Atlantic Oscillation (Moreno et al 2012;Luning et al 2019).…”
Section: Pre-lia Glacial Evolutionmentioning
confidence: 99%
“…For most areas in the world, particularly in the northern hemisphere, this process of cooling culminated during the Little Ice Age (LIA), whose generally accepted time span is between 1300 and 1850 AD (e.g., Holzhauser et al 2005;Joerin et al 2006;Wanner et al 2008Wanner et al , 2011Geirsdóttir et al 2009;Ivy-Ochs et al 2009;Nesje et al 2009;Le Roy et al 2015;Solomina et al 2016a;. Nevertheless, from the beginning of the Neoglacial until the onset of the LIA, the climate underwent other fluctuations, including the cooling of the Bronze Age, the warm Roman Period, the cold Dark Ages during the early Middle Ages (e.g., Holzhauser et al 2005;Wanner et al 2008Wanner et al , 2011Ivy-Ochs et al 2009), and the Medieval Climate Anomaly (MCA), characterized by sustained and relatively intense warming (Moreno et al 2012;Luning et al 2019). In a more detailed approach, even the LIA cannot be considered as a homogeneous, constantly cold period, since cold waves alternated with droughts and hot waves , thus confirming that the Holocene has been subjected to continuous climate variability.…”
Section: Introductionmentioning
confidence: 99%